Upconversion studies in rare earth ions-doped lanthanide materials - Singh A.K.; Kumar K.; Rai S.B. (My University, 2025)
In the present work, results of upconversion emission in various powder samples have been discussed. The powder upconversion phosphors such as La2O3:Er3+ /Yb3+, LaF3:Er3+ /Yb3+, CeO2 :Er3+/Yb3+, CeF3 :Er3+ /Yb3+ were prepared and their upconversion emission, using 976 nm wavelength excitation, was investigated in depth. These phosphors have shown good upconversion emission in the visible region except for the CeF3:Er3+ /Yb3+ phosphor. Two intense bands around 525 and 550 nm due to the 2H11/2 →4 I15/2 and 4S3/2 →4 I15/2 transitions, respectively, are found to be in a thermally coupled state in these samples. The intensity ratio of these two bands permitted us to estimate the temperature of the environment. The pump power studies of the emission bands of these samples are also made to understand the dynamics of the upconversion emission. © Indian Academy of Sciences.